36‐2: Optimizing Brightness with Micro Lens Array Gain Enhancing Films for Edge‐Lit Back Light Units. Issue 1 (28th June 2022) - Shen, Bing; Walker, Kenneth L.; Pope, Matthew
Abstract : The on‐axis brightness of a conventional edge‐lit back light unit (BLU) was optimized by replacing the conventional down diffuser with a Micro Lens Array (MLA) gain enhancing diffuser (GEF). It was found that the brightness could be increased ~29% by using a GEF with a 90 degree apex angle prism facing the light guide plate (LGP) and pyramidal structures on the backside of the GEF. The angular orientation of the prism relative to the cross brightness enhancing films (xBEF) and the orientation ofthe xBEF relative to the light propagation direction is critical. Different edge‐lit BLUs will require different MLA‐based GEF to maximize brightness.